2017
DOI: 10.1158/0008-5472.can-17-2321
|View full text |Cite
|
Sign up to set email alerts
|

TLR4-Mediated Inflammation Promotes KSHV-Induced Cellular Transformation and Tumorigenesis by Activating the STAT3 Pathway

Abstract: Toll-like receptors (TLR) are conserved immune sensors mediating antimicrobial and antitumoral responses, but recent evidence implicates them in promoting carcinogenesis in certain cancers. Kaposi’s sarcoma (KS) is caused by infection of Kaposi’s sarcoma-associated herpesvirus (KSHV) and is characterized by uncontrolled neoangiogenesis and inflammation. Here we show that TLR4 is upregulated in KSHV-infected spindle tumor cells in human KS lesions. In a model of KSHV-induced cellular transformation, KSHV upregu… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
45
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(52 citation statements)
references
References 49 publications
6
45
1
Order By: Relevance
“…Altered oral microbiota has been observed in several diseases including diabetes, bacteremia, endocarditis, cancer and autoimmune disease, and in some cases can influence disease progression [27] or tumor response to immunotherapy [28]. Furthermore, we previously demonstrated that TLR4 stimulation with LPS from either E. coli strain K12 or C25 promoted KSHVinduced cellular transformation and tumorigenesis in a KS-like animal model [20]. Therefore, the purpose of this study was to investigate whether oral KS was associated with an alteration of the bacterial microbiota in the oral cavity.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…Altered oral microbiota has been observed in several diseases including diabetes, bacteremia, endocarditis, cancer and autoimmune disease, and in some cases can influence disease progression [27] or tumor response to immunotherapy [28]. Furthermore, we previously demonstrated that TLR4 stimulation with LPS from either E. coli strain K12 or C25 promoted KSHVinduced cellular transformation and tumorigenesis in a KS-like animal model [20]. Therefore, the purpose of this study was to investigate whether oral KS was associated with an alteration of the bacterial microbiota in the oral cavity.…”
Section: Discussionmentioning
confidence: 97%
“…Some enterotoxic Escherichia coli (E. coli) strains are associated with tumorigenesis in mouse models of colorectal cancers [19]. We have recently shown that E. coli C25 strain could promote KSHV-induced tumorigenesis in a KSlike mouse model [20].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Notably, PDGFR-β is known to induce STAT3 phosphorylation, and activated STAT3 leads to cell transformation [47,48]. Consequently, elevated STAT3 signaling inhibits apoptosis and supports cancer survival, producing a phenotype similar to chemo-resistance [49].…”
Section: Discussionmentioning
confidence: 99%
“…Oncogenic receptor ALK belongs to an insulin receptor (IR) or oncogenic receptor IGF-1R family [127]. TLR4 stimulation with its ligand lipopolysaccharides promotes KSHV-induced cellular transformation and tumorigenesis by activating the STAT3 pathway [128] TLR4 mediated tumorigenesis while TLR4 antagonist CL1095 inhibite it. Toll-like receptor (TLR4) induced pro-oncogenic or also protumoral function in head and neck carcinoma [129].…”
Section: Dietary Iodine Intake and The Prevalence Of Papillary Carcinmentioning
confidence: 99%